PENGARUH KOMPETENSI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI PADA DINAS PEMUDA DAN OLAHRAGA PROVINSI SUMATERA BARAT - Novi Yanti; Defi Afriani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the effect of Competence and Emotional Intelligence on Employee Performance at the officeDinasPemudadanOlahragaProvinsi Sumatera Barat. Employees are a very important part in the process of determining Employee Performance. This research was conducted at the DinasPemudadanOlahragaProvinsi Sumatera Barat by using all employees as research respondents. The population in this study were all many as 71 people samples taken from the population using the method (1) interview (2) questionnaire and analyzed by multiple liner analysis SPSS program (statistical product and service solution) V.21.0 Results This study shows that the results of employees of the West Sumatra Province Youth and Sports Service as the T test of competency do not affect the performance of employees this is evident from the significance value of 0.581> 0.05 variable Emotional Intelligence 0.000